Review of Soil and Water Assessment Tool (SWAT) applications in Brazil: Challenges and prospects - Bressiani, Danielle de Almeida; Gassman, Philip W.; Fernandes, Josimar Gurgel; Garbossa, Luis Hamilton Pospissil; Srinivasan, Raghavan; Bonumá, Nadia Bernardi; Mendiondo, Eduardo Mario (International Journal of Agricultural and Biological Engineering, 2015)
The geographical extent of Brazil exceeds 8.5 million km2 and encompasses a complex mix of biomes and other environmental conditions. Multiple decision support tools are needed to help support management of these diverse Brazilian natural resources including ecohydrological models. The use of the Soil and Water Assessment Tool (SWAT) ecohydrological watershed-scale model in Brazil has increased greatly during the past decade. Well over 100 SWAT studies were identified in this review which have been published during 1999 to 2015 in Brazilian and international journals, conference proceedings, and as theses or dissertations, many of which are written in Portuguese. The majority of these studies (102 total) are reviewed here as part of an extensive survey covering the 1999 to 2013 time period. Temporal and spatial distributions, a summary of hydrologic calibration and validation results and a synopsis of the types of applications that were performed are reported for the surveyed studies. A smaller subset of recent Brazilian studies published in English between 2012 and 2015 in scientific journals are also reviewed, with emphasis on hydrologic and sediment transport testing results as well as scenario applications that were performed. The majority of the surveyed SWAT studies was performed for watersheds located in the South and Southeast regions of Brazil (67%) and was conducted in the context of academic research. Nearly 50% of the surveyed studies reported only hydrologic results. Similar trends were found for the subset of more recent English publications. Limited studies have been reported that describe applications of SWAT in Brazil by private firms or government agencies; this review indicates that the potential exists for increased numbers of such studies in the future. However, there is evidence that a lack of accessibility to adequate quality input data is a possible hindrance to the more general use of SWAT for watershed applications in Brazil. Keywords: SWAT, models, mapping applications, review, Brazil DOI: 10.3965/j.ijabe.20150803.1765 Online first on [2015-05-31] Citation: Bressiani D A, Gassman P W, Fernandes J G, Garbossa L H P, Srinivasan R, Bonumá N B, et al. Review of Soil and Water Assessment Tool (SWAT) applications in Brazil: Challenges and prospects. Int J Agric & Biol Eng, 2015; 8(3): 9－35.